2010
DOI: 10.1063/1.3369450
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of copper nitride thin films: The role of nitrogen migration

Abstract: The atomic composition, structural, morphological, and optical properties of N-rich copper nitride thin films have been investigated prior to and after annealing them in vacuum at temperatures up to 300°C. Films were characterized by means of ion-beam analysis ͑IBMA͒, X-ray diffraction ͑XRD͒, atomic force microscopy ͑AFM͒, and spectroscopic ellipsometry techniques ͑SE͒. The data reveal that even when the total ͑integrated over the whole thickness͒ atomic composition of the films remains constant, nitrogen star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
(35 reference statements)
1
34
0
Order By: Relevance
“…The beam current density was selected to prevent temperature enhancements higher than around 50 °C, which is clearly below to the reported values to observe significant nitrogen depletion [16]. Moreover, X-ray diffraction data on similar samples heated up to 300 °C [6] evidences no sample decomposition. Therefore, it can be concluded that the beam-induced temperature enhancement does not play a significant role in the described mechanism.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The beam current density was selected to prevent temperature enhancements higher than around 50 °C, which is clearly below to the reported values to observe significant nitrogen depletion [16]. Moreover, X-ray diffraction data on similar samples heated up to 300 °C [6] evidences no sample decomposition. Therefore, it can be concluded that the beam-induced temperature enhancement does not play a significant role in the described mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenological model has been also used to describe high sputtering yields in several other materials (oxides, halides) when irradiated in the electronic regime. Nevertheless, a recent publication [6] has shown that the nitrogen sputtering yield in copper nitride films is independent of substrate temperature during irradiation within the 100-300 °C range. This feature cannot be properly explained on the basis of the thermal spike model [19] since it would predict an enhancement of the damage track radius produced by each impact with temperature and thus, an increase in the overall sputtering yield.…”
Section: R{#)mentioning
confidence: 99%
See 1 more Smart Citation
“…A main problem that has been addressed concerns the location of the excess N atoms, that has been, so far, a matter of controversy. Experimental data [27] have revealed that for films sputtered under the same conditions, extra nitrogen (or at least a high fraction of it) incorporates in the film in interstitial positions forming a solid solution and expanding the crystal lattice in comparison to stoichiometric Cu 3 N. Moreover, spectroscopic ellipsometry and infrared absorption measurements carried out on N-rich Cu 3 N films have clearly indicated the presence of a free-carrier contribution in the optical spectra that has been related to the N excess [26]. The origin and nature of those extra carriers could not be elucidated in that work, partly due to the difficulty of carrying out reliable Hall measurements and the dispersion of so far reported data [23,28], In order to clarify the experimental situation and to assess the electronic role of the excess N in Cu 3 N experiments: electrical conductivity, spectroscopic ellipsometry at several temperatures and [23,28], that have not, so far, provided conclusive results.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these theoretical predictions have not been, corroborated by experiments, very probably because of the instability of the Cu 3 N 2 compounds, which as far as we know have not been hitherto synthesized. An extensive research effort [10,26,27] has been recently devoted to understand the structure and physical properties of N-rich films, whose stoichiometry has been well characterized by means of ion beam analysis techniques. A main problem that has been addressed concerns the location of the excess N atoms, that has been, so far, a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%